Presence of Prisoners with Mental Health Prisoners in Detention and Correctional Centers in the Republic of Kosovo - Hajdari, Niman (Torture Journal, 2024)
Conventions adopted by the United Nations and Council of Europe pay special importance to the treatment of prisoners with mental health problems. Their treatment is closely related to respect for human dignity, torture, cruel and degrading treatment or punishment. The European Court of Human Rights, in many cases, has ruled that the detention of a mentally-ill person can raise issues from Article 3 of the European Convention on Human Rights and that the lack of adequate medical care can result in treatment contrary to this article, especially with regard to inhumane and degrading treatment or punishment. The Republic of Kosovo is not a member of the United Nations and Council of Europe. However, it has incorporated in its Constitution a number of Conventions adopted by the United Nations and Council of Europe, which are very important international instruments for the protection of Human Rights and Fundamental Freedoms. Also, Kosovo has adopted a legal frame work which prohibits torture, cruel and degrading treatment or punishment in accordance with the international Human Rights standards. The Constitution, also provides that Human Rights and Fundamental Freedoms guaranteed by the Constitution shall be interpreted in accordance with the case law of the European Court of Human Rights. This paper is based on the reports of international Human Rights monitoring mechanisms and their findings regarding treatment of prisoners with mental health problems, such as Council of Europe Committee for the Prevention of Torture, Ombudsperson of Kosovo reports, reports of governmental bodies, as well as reports of Kosovo NGOs, which are authorized to monitor Human Rights situation in places of deprivation of liberty. Based on Ombudsperson’s reports, Committee for the Prevention of Torture reports, reports of Prison Health Department of Kosovo Ministry of Health, as well as reports of the NGOs in Kosovo, the treatment of prisoners with serious mental problems in detention and correctional centers in the Republic of Kosovo remains a serious challenge, despite the efforts of the competent authorities to change this situation and to increase human and institutional capacities. Prisoners with serious mental health problems continue to be accommodated in detention and correctional centers, instead of being accommodated in the relevant health institutions, due to the lack of institutional capacities and personnel. Key words: Human Rights, mentally ill prisoners, international standards, applicable legislation in Kosovo